Efficiency of bank branches: empirical evidence from a two-phase research approach - Cvetkoska, Violeta; Savic, Gordana (Taylor & Francis Group, 2017)
The aim of this paper is to assess the relative efficiency of the branches of Komercijalna Banka AD Skopje during a three-year period (from 2009 to 2011). The research sample consists of eight branches performing the same financial activities during the reporting period. The mathematical technique DEA window analysis was used in the first phase in order to allow monitoring of the trend of the relative efficiency of each branch under consideration. From the bank management point of view, unexpected results were obtained in this phase; to validate the results the AHP-DEA validation model was proposed and used in the second phase. The management verified the obtained results claiming they were especially valuable in the process of making justifiable decisions for the further successful performance of the bank.
Keywords: Bank branches; relative efficiency; DEA window analysis; AHP